2015
DOI: 10.1016/j.paid.2015.06.017
|View full text |Cite
|
Sign up to set email alerts
|

Intelligence and finance

Abstract: This paper explore the effect of intelligence on financial development using data from 180 nations, over the period 2000-2012. The results provide strong support for the claim that intelligence is positively associated with the supply of finance to economy. This paper establishes that, moving from country with the mean IQ score (84.1) to the highest national IQ score (107.1) is associated with 3.6 fold increase in the size of banking sector. The positive effect of intelligence remains intact when we control fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 40 publications
0
13
0
Order By: Relevance
“…(2009) ample cross-country studies document the impact of legal origins on institutions, corruption, financial development and gender inequality (Albouy, 2012;La Porta et al, 2008;Jayachandran, 2015;Salahodjaev, 2015c). For instance Potrafke & Ursprung (2012) find that gender institutions are stronger in nations with communist common laws as compared to nations with English common law.…”
Section: Control Variablesmentioning
confidence: 99%
“…(2009) ample cross-country studies document the impact of legal origins on institutions, corruption, financial development and gender inequality (Albouy, 2012;La Porta et al, 2008;Jayachandran, 2015;Salahodjaev, 2015c). For instance Potrafke & Ursprung (2012) find that gender institutions are stronger in nations with communist common laws as compared to nations with English common law.…”
Section: Control Variablesmentioning
confidence: 99%
“…Firstly, it is well acknowledged that countries with higher average IQ will experience a higher level of socioeconomic development. As outcomes of their more-positive cultures, high IQ societies are associated not only with higher economic growth and productivity (Jones & Schneider, 2006, but also with greater institutional quality such as less corruption, less inequality of gender, enhanced financial development, more democratic regime and political freedom, more efficient bureaucracies, and better rule of law (Lynn & Vanhanen, 2012;Potrafke, 2012;Salahodjaev, 2015;Salahodjaev & Azam, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…(Hunt & Wittman, 2008 p. 1). In addition, studies have also shown that intelligence is robustly related to shadow economy (Salahodjaev, 2015a), financial development (Salahodjaev, 2015b), corruption (Potrafke, 2012), sustainability (Salahodjaev, 2016a) anddeforestation (2016b) To mitigate the potential omitted variable bias, we include a vector of bio-geography control variables. Masters & MacMillan (2001) explore the role of geography and climate in convergence of income across the globe.…”
Section: Research Methods and Data Sourcesmentioning
confidence: 99%